Spatial specification and reasoning using grammars: from theory to application. Issue 4 (2nd October 2018) - Liu, Yufeng; Zhang, Kang; Kong, Jun; Zou, Yang; Zeng, Xiaoqin
ABSTRACT: This article reviews grammatical formalisms that are capable of supporting spatial specification and reasoning, or spatial-enabled grammars, and their wide range of applications. The review takes two typical grammars, i.e., shape grammar and spatial graph grammar, as concrete representatives to consider connectivity and spatial relations in the parsing and generating processes. This article proposes four aspects as a set of criteria to compare the commonality and differences among spatial-enabled grammars, i.e., parsing and generation, granularity of spatial specification, form of spatial specification, and 2D and 3D modeling. Finally, further developments related to spatial-enabled grammars are discussed.